The Therapeutic Potential of Novel Carnosine Formulations: Perspectives for Drug Development - Angela Bonaccorso; Anna Privitera; Margherita Grasso; Sonya Salamone; Claudia Carbone; Rosario Pignatello; Teresa Musumeci; Filippo Caraci; Giuseppe Caruso (Pharmaceuticals, 2023)
Carnosine (beta-alanyl-L-histidine) is an endogenous dipeptide synthesized via the activity of the ATP-dependent enzyme carnosine synthetase 1 and can be found at a very high concentration in tissues with a high metabolic rate, including muscles (up to 20 mM) and brain (up to 5 mM). Because of its well-demonstrated multimodal pharmacodynamic profile, which includes anti-aggregant, antioxidant, and anti-inflammatory activities, as well as its ability to modulate the energy metabolism status in immune cells, this dipeptide has been investigated in numerous experimental models of diseases, including Alzheimer’s disease, and at a clinical level. The main limit for the therapeutic use of carnosine is related to its rapid hydrolysis exerted by carnosinases, especially at the plasma level, reason why the development of new strategies, including the chemical modification of carnosine or its vehiculation into innovative drug delivery systems (DDS), aiming at increasing its bioavailability and/or at facilitating the site-specific transport to different tissues, is of utmost importance. In the present review, after a description of carnosine structure, biological activities, administration routes, and metabolism, we focused on different DDS, including vesicular systems and metallic nanoparticles, as well as on possible chemical derivatization strategies related to carnosine. In particular, a basic description of the DDS employed or the derivatization/conjugation applied to obtain carnosine formulations, followed by the possible mechanism of action, is given. To the best of our knowledge, this is the first review that includes all the new formulations of carnosine (DDS and derivatives), allowing a decrease or complete prevention of the hydrolysis of this dipeptide exerted by carnosinases, the simultaneous blood–brain barrier crossing, the maintenance or enhancement of carnosine biological activity, and the site-specific transport to different tissues, which then offers perspectives for the development of new drugs.